Dietary Approaches to Stop Hypertension (DASH) diet: applicability and acceptability to a UK population. - Harnden, K; Frayn, K; Hodson, L (2010)
BACKGROUND: The Dietary Approaches to Stop Hypertension (DASH) diet is widely promoted in the USA for the prevention and treatment of high blood pressure. It is high in fruit and vegetables, low-fat dairy and wholegrain foods and low in saturated fat and refined sugar. To our knowledge, the use of this dietary pattern has not been assessed in a free-living UK population. METHODS: The DASH diet was adapted to fit UK food preferences and portion sizes. Fourteen healthy subjects followed the adapted DASH diet for 30 days in which they self-selected all food and beverages. Dietary intake was assessed by 5-day food diaries completed before and towards the end of the study. Blood pressure was measured at the beginning and end of the study to assess compliance to the DASH style diet. RESULTS: The DASH diet was easily adapted to fit with UK food preferences. Furthermore, it was well tolerated and accepted by subjects. When on the DASH style diet, subjects reported consuming significantly (P < 0.01) more carbohydrate and protein and less total fat (5%, 6% and 9% total energy, respectively). Sodium intakes decreased by 860 mg day(-1) (P < 0.001). Systolic and diastolic blood pressure decreased significantly (P < 0.05) by 4.6 and 3.9 mmHg, respectively when on the DASH style diet. CONCLUSIONS: The DASH style diet was well accepted and was associated with a decrease in blood pressure in normotensive individuals and should be considered when giving dietary advice to people with elevated blood pressure in the UK.